Leaving room in the CBD's ABS protocol for the future development of specialized access and benefit-sharing arrangements: The example of agricultural microbial genetic resources - CGIAR Systemwide Genetic Resources Programme (2010)
Since 2004, Bioversity International, through the CGIAR’s System-wide Genetic Resources Programme (SGRP), has contributed to the ongoing negotiations of a protocol on access and benefit-sharing under the Convention on Biological Diversity (CBD). This policy brief highlights the importance of maintaining flexibility in the protocol to develop future specialized international arrangements for access and benefit-sharing for different types of genetic resources. It presents the example of agricultural microbial genetic resources (AMiGR).